KSHEERALASAKA VIS-À-VIS COW’S MILK ALLERGY: A CRITICAL REVIEW - Antony, Chris (International Journal of Ayurveda and Pharma Research, 2018)
Ksheeralasaka is a multi-system disease of the breast-fed child caused by Sannipataja-stanya-dushti (breast milk vitiated by all the Tridoshas). A proper understanding of the condition is not available and it is confused with lactose intolerance and cow’s milk allergy. Hence a thorough review of Ksheeralasaka and its management in the light of Ayurvedic and modern principles is intended in this paper so that suitable therapies can be selected. Ksheera denotes breast milk and Alasaka is a type of Ajeerna (indigestion), a condition called Ama caused by Agnimandya or weak digestive/metabolic power. Thus Ksheeralasaka is Ajeerna or indigestion in the infant caused by intake of vitiated breast milk. Ksheeralasaka is most similar to non-IgE-mediated cow’s milk protein allergy and is also comparable with food allergies caused by egg, peanuts, etc. Lactose intolerance and lactose overload can also co-occur with cow’s milk protein allergy or food allergies. Being a disease of Ama and Stanyadushti, Apatarpana (depletion) in the form of Sodhana (purification) and Stanyasodhana (purification of breast milk) are the treatments to be adopted. Langhana or fasting is sufficient if Ama is mild, Langhana and Pachana (digestives) are needed if it is moderate and Sodhana (purification) is needed if severe. Vamana for mother and child purifies the gut and expels the allergens ingested. Breast milk purifiers and anti-diarrhoeals are judiciously advised for the mother and the child respectively. Advice regarding feeding practices can help reduce symptoms of lactose overload that may co-occur.